ETIKA GURU DALAM KITAB ADAB AL ‘ALIM WAL AL MUTA’ALIM DAN RELEVANSINYA DENGAN KOMPETENSI GURU - Imam Setiawan; Rosichin Mansur; Moh Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study is motivated by the importance of tutor’s role as an educator, where teachers or educators currently take Many actions that are not reflected as teachers. This is important, because educators are a good reflection and a model for students and the community. This study is intended to answer problems that often occur in teacher behavior. By trying to present the personality of the teacher from the perspective of the Islamic education figure KH Hasyim Asyari in the book of adab al 'Alim wa al muta'allimThis research was made by the author with the aim of describing the ethics of teachers towards students according to the book of Adab al 'Alim wa al- Muta'allim. As well as to describe what teacher ethics are like towards their lessons in the book of Adab al 'Alim wa al-Muta'allim, and to describe the relevance of teacher ethics in the book of Adab al 'Alim wa al- Muta'allim with teacher competence, according to KH Hasyim Asy'ari contained in his book namely adab al 'Alim wa al muta'allim. The writing method used in this study is a qualitative method, more precisely the library search method, namely to examine primary ideas on the scope of the problem considered by relevant secondary ideas. The main source of this research is the Book of Adab al 'Alim wa al-Muta'allim by KH Hasyim Asy'ari, and also uses secondary sources, namely sources of books, journals and other scientific works that have relevance to the discussion of research related to research. which is conducted. The data analysis method uses the descriptive analysis method, namely the analysis to express the ideas studied and the interpretation of data as followers in the expression of opinions.The results of this study indicate that the teacher ethics formulated by Hasyim Asyari in adab al 'Alim wa al muta'allim shows that: teachers must have good ethics and adab to be role models for students and society, and, stick to the sunnah, fight bids. and istiqamah in worship, having noble character, developing knowledge. The teacher ethics formulated by KH Hasyim Asy'ari can be relevant to the competence of teachers in Permendiknas number 16 of 2007 so that they are able to control teacher behavior so as not to commit immoral or deviant actions.